2019
DOI: 10.1186/s41747-019-0111-8
|View full text |Cite
|
Sign up to set email alerts
|

Two-centre comparative experimental study of biparametric MRI at 3.0 T with and without endorectal coil using kiwifruit (Actinidia deliciosa) as a phantom for human prostate

Abstract: Background Application of an endorectal coil (ERC) for 3.0-T prostate magnetic resonance imaging (MRI) is contentious. We hypothesised that a multicoil phased-array protocol provides T2-weighted images (T2WI) and diffusion-weighted images (DWI) with reduced field-of-view (DWI reduced ) and monoexponential apparent diffusion coefficient (ADC) maps that are technically equivalent with ERC or without ERC (noERC). Methods Axial T2WI (repetition ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These observations have been confirmed by several published studies [9,10,13]. Different correction algorithms have been developed to compensate signal inhomogeneity, but these may lead to noise level variation and an increase of acquisition time [11,12,29]. It has to be considered that rectal gas if present may lead to similar susceptibility artifacts as gas in ERC.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…These observations have been confirmed by several published studies [9,10,13]. Different correction algorithms have been developed to compensate signal inhomogeneity, but these may lead to noise level variation and an increase of acquisition time [11,12,29]. It has to be considered that rectal gas if present may lead to similar susceptibility artifacts as gas in ERC.…”
Section: Discussionmentioning
confidence: 72%
“…ERCs were previously considered indispensable when patients were scanned using 1.5 T MR scanners. However, several recent studies revealed comparable image quality and similar prostate cancer detection rates with or without ERCs using modern 3 T MR scanners and surface pelvic phased-array receiver coils [10,[12][13][14][15][16][17]. One potential limitation of prior studies is that all radiologists comparing the different coil setups came from the same or closely connected institutions, which may have influenced their quality assessment in favor of the routinely utilized technique in these institutions [9,10,13].…”
Section: Introductionmentioning
confidence: 99%